Of Cigarettes, High Heels, and Other Interesting Things - Danesi, Marcel. author. aut Link
XI, 235 p.
Keywords: Why do people routinely risk their health by smoking cigarettes? Why do some females make walking a struggle by donning high heels? In a fully updated edition, the author attempts to answer such questions by explaining the discipline that endeavors to understand the human meaning quest: semiotics.